EFEK KONSUMSI JUS TOMAT DAN JUS JAMBU BIJI TERHADAP KADAR HEMOGLOBIN PADA SISWI REMAJA PENDERITA ANEMIA - Ida Widaningsih; Ika Kania Fatdo Wardani; Hajar Nur Fathur Rohmah; Neneng Julianti (JOMIS (Journal of Midwifery Science), 2026)
Anemia remains a significant nutritional challenge in Indonesia, with national data (Riskesdas 2018) indicating a prevalence of 32% among adolescent girls. Globally, the WHO estimates that approximately 40% of adolescent girls in developing countries are affected by anemia, with iron deficiency anemia as the predominant cause. The condition carries extensive consequences for physical growth, learning capacity, and future reproductive health. Utilizing locally accessible food resources is regarded as a feasible and enduring approach to improving hemoglobin status. This study aimed to evaluate the combined effect of tomato juice and guava juice consumption on hemoglobin levels among anemic adolescent girls. A quasi-experimental design with a single-group pretest-posttest approach was employed on 30 adolescent girls aged 10–19 years in Wanajaya Village, Bekasi Regency. Participants were recruited through purposive sampling based on predefined inclusion criteria. Hemoglobin levels were assessed using a portable hemoglobinometer at two time points: before and after the intervention period. The Wilcoxon signed-rank test was applied for statistical analysis. Findings demonstrated a reduction in anemia prevalence from 60% (18 participants) pre-intervention to 26.7% (8 participants) post-intervention, with 73.3% of participants achieving normal hemoglobin levels. The Wilcoxon test yielded Asymp. Sig. = 0.002 (p < 0.05), with 10 participants showing hemoglobin increases (Mean Rank 5.50) and no participants recording a decline (Negative Rank = 0). The study concludes that the combination of tomato juice and guava juice significantly improves hemoglobin levels and may serve as an effective food-based intervention for managing anemia in adolescent girls